Penataan Ruang Pameran Seni Lintas Batas - Mahendra, I Komang Aditya; Sujana, I Wayan; Jodog, I Made (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2023)
The arrangement of an exhibition space is the main focus raised in the writing of this thesis with the title "Spatial Arrangement of Cross-border Art Exhibitions" from an observation of spatial arrangement in the previous exhibition "Makna Murni; Two Sides” in terms of spatial planning, display, lighting and circulation which is carried out without being organized. From these problems the author finally wrote an article which contained procedures for designing exhibition space arrangements, room and work lighting, work display, and circulation of exhibition visitors and also discusses making spatial planning not only display and arrange the room but also manipulate the mood of exhibition visitors so that they get the impression when visiting the exhibition that the author designed, the purpose of this thesis work is to provide an understanding of spatial arrangement, work, light and visitor circulation and also Hopefully it will be useful in the arrangement of exhibition space. The design of this art exhibition was carried out at the Arshika hotel, an exhibition room with a different type and using natural and artificial lighting to illuminate the works on display.